Utilization of modern contraceptives and associated factors among women of homeless reproductive age in Adama town, Oromia, Ethiopia - Gemechu Dereje Feyissa; Seble Belihu; Tamrat Endebu (BMC, 2024)
Abstract Background Family planning refers to a conscious effort by a couple to limit or space the number of children they have through the use of contraceptive methods. Contraceptive utilization is a practice that helps individuals or couples avoid unwanted pregnancy. A lack of family planning puts homeless individuals at a higher risk of unwanted pregnancies and sexually transmitted infections. However, there is little data about modern contraceptive utilization among homeless women in the study area. Objectives It has aimed to assess the utilization of modern contraceptives and associated factors among homeless reproductive-age women in Adama town, 2023. Methods A community-based cross-sectional study was conducted in Adama town among 286 homeless women. A convenience sampling technique was used. The data were collected through face-to-face interviews using a pretested structured questionnaire. The collected data were cleaned, coded, and entered into Epi Info, and the data were exported to the Statistical Package for Social Sciences (SPSS) version 22. Descriptive statistics were used to characterize the study population. The associations between dependent and independent variables were modeled using binary logistic regression. The adjusted odds ratio (AOR) and 95% confidence interval (CI) were used to estimate associations, and a P value < 0.05 was considered to indicate statistical significance. Results Out of the planned 289 respondents, 286 (98.9%) were participated. The prevalence of modern contraceptive utilization was 56.6% [95% CI: (50.7, 62.2)]. Among the utilizers, implants (52.5%), injectables (42%), and pills (5.5%) were used. Homeless women aged 25-34 years [AOR = 4.22, 95% CI: (1.77, 10.05)], a formal education [AOR = 3.04, 95% CI: (1.21, 7.60)], a slept off-street [AOR = 2.81, 95% CI: (1.25, 6.34)], a monthly income greater than or equal to 2400 Ethiopian birr [AOR = 4.18, 95% CI: (2.11, 8.29)], a sexual intercourse AOR = 3.14, 95% CI: (1.17, 8.40)], and a history of pregnancy after joining the street life [AOR = 9.21, 95% CI: (3.67, 23.12)] were factors significantly associated with the utilization of modern contraceptives. Conclusion The prevalence of modern contraceptive utilization among homeless women was relatively higher than in previous studies. The associated factors for contraceptive utilization included age, education, place for sleeping, income, sexual intercourse and history of pregnancy after joining the street life. The Regional and Adama town Health Bureau and facilities should develop targeted interventions (considering age, educational, and other disparities) to reduce the unmet need for modern contraception and halt unnecessary health outcomes among homeless women, their children, and families.